Oral Cannabidiol Prevents Allodynia and Neurological Dysfunctions in a Mouse Model of Mild Traumatic Brain Injury - Belardo, Carmela; Iannotta, Monica; Boccella, Serena; Rubino, Rosamaria Cristina; Ricciardi, Flavia; Infantino, Rosmara; Pieretti, Gorizio; Stella, Luigi; Paino, Salvatore; Marabese, Ida; Maisto, Rosa; Luongo, Livio; et al. (Frontiers in Pharmacology, 2019)
Neurological dysfunctions are the most impactful and persistent consequences of traumatic brain injury (TBI). Indeed, previous reports suggest that an association between TBI and chronic pain syndromes, as well anxio-depressive behaviors, tends to be more common in patients with mild forms of TBI. At present, no effective treatment options are available for these symptoms. In the present study, we used a weight drop mild TBI mouse model to investigate the effect of a commercially available 10% Cannabidiol (CBD) oil on both the sensorial and neuropsychiatric dysfunctions associated with mild TBI through behavioral and biomolecular approaches. TBI mice developed chronic pain associated with anxious and aggressive behavior, followed by a late depressive-like behavior and impaired social interaction. Such behaviors were related with specific changes in neurotransmitters release at cortical levels. CBD oral treatment restored the behavioral alterations and partially normalized the cortical biochemical changes. In conclusion, our data show some of the brain modifications probably responsible for the behavioral phenotype associated with TBI and suggest the CBD as a pharmacological tool to improve neurological dysfunctions caused by the trauma.